1996
DOI: 10.2527/1996.7471481x
|View full text |Cite
|
Sign up to set email alerts
|

Mass selection for 70-day body weight in rabbits.

Abstract: Five generations of phenotypic mass selection for increased 70-d body weight (market age, MW) were conducted in an experimental population of rabbits. Market-age weight was recorded for 1,616 rabbits from 336 litters (sired by 121 bucks and reared by 321 does). Additional growth and carcass traits measured in control (C) and select (S) lines were 28-d weaning weight (WW), 28- to 70-d average daily gain (ADG), carcass yield percentage (CY), loin primal cut percentage (LP), and lean-to-bone ratio in the loin pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
35
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 24 publications
14
35
0
5
Order By: Relevance
“…Similarly, the estimated heritability value for ADG between 4 and 9 wk was very similar to the value reported by Piles et al [28], but was slightly higher than that reported in rabbits selected on 70-d mass weight (0.17, [18]) or for 4 to 10 wk ADG (0.23, [34]). The high positive genetic correlation between 63-d body weight and 4 to 9 wk ADG, was close to that reported between 70-d body weight and 3-4 to 10 wk ADG (r g = 0.91 to 0.98, [18,40]). Indeed, a moderate correlated response (r g = 0.50 to 0.64) for weaning weight in rabbits selected on market body weight has been reported previously [18,22]).…”
Section: Genetic Parameters For Growth Performance and Qualitative Trsupporting
confidence: 86%
See 4 more Smart Citations
“…Similarly, the estimated heritability value for ADG between 4 and 9 wk was very similar to the value reported by Piles et al [28], but was slightly higher than that reported in rabbits selected on 70-d mass weight (0.17, [18]) or for 4 to 10 wk ADG (0.23, [34]). The high positive genetic correlation between 63-d body weight and 4 to 9 wk ADG, was close to that reported between 70-d body weight and 3-4 to 10 wk ADG (r g = 0.91 to 0.98, [18,40]). Indeed, a moderate correlated response (r g = 0.50 to 0.64) for weaning weight in rabbits selected on market body weight has been reported previously [18,22]).…”
Section: Genetic Parameters For Growth Performance and Qualitative Trsupporting
confidence: 86%
“…The high positive genetic correlation between 63-d body weight and 4 to 9 wk ADG, was close to that reported between 70-d body weight and 3-4 to 10 wk ADG (r g = 0.91 to 0.98, [18,40]). Indeed, a moderate correlated response (r g = 0.50 to 0.64) for weaning weight in rabbits selected on market body weight has been reported previously [18,22]). Interestingly, the common (litter) effect was markedly larger than the direct additive effect for weaning weight, in accordance with Lukefahr et al [18].…”
Section: Genetic Parameters For Growth Performance and Qualitative Trsupporting
confidence: 83%
See 3 more Smart Citations